Study on the Effect of Radish Sprouts on Short-Chain Fatty Acids and Gut Microbial Diversity in Healthy Individuals - Ru Li; Xuehong Chen; Cong Shi; Yi Zhu (Foods)
This study aimed to assess the impact of radish sprouts on the gut microbiota of healthy individuals. Radish sprout additives, subjected to short-term storage and steam treatment, were used to intervene in an in vitro culture of human gut microbiota. The influence of radish sprouts on the gut microbiota was evaluated by monitoring short-chain fatty acid (SCFA) content and proportion in the fermentation broth, and microbial diversity was assessed using 16S rDNA amplicon sequencing. The results indicated that the gut microbiota produced a substantial amount of SCFA within 48 h of fermentation, with a right-skewed distribution across all groups. The addition of both digestates enhanced Firmicutes diversity, while Bacteroidetes and Proteobacteria diversity remained stable between the control and fresh sprout groups. The 30 s steam treatment group showed an increase in Bacteroidetes and a decrease in Proteobacteria diversity. The abundance of Bacilli, Bacillaceae, and Bacillus was significantly higher in both the fresh and steam-treated groups compared to the control. Both fresh and steam-treated radish sprout digestates enriched gut microbiota diversity, with steam treatment showing superior effects. These findings suggest that radish sprout consumption may positively influence gut microbiota, with steam treatment potentially enhancing these benefits.